Short-term ambient particle radioactivity level and renal function in older men: Insight from the Normative Aging Study - Gao, X.; Koutrakis, P.; Blomberg, A. J.; Coull, B.; Vokonas, P.; Schwartz, J.; Baccarelli, A. A. (Environ Int, 2019)
{BACKGROUND: Whole-body and thoracic ionizing radiation exposure are both associated with the development of renal dysfunction. However, whether low-level environmental radiation from air pollution affects renal function remains unknown. OBJECTIVES: We investigated the association of particle radioactivity (PR) with renal function defined by the estimated glomerular filtration rate (eGFR) and chronic kidney disease (CKD) in the Normative Aging Study. METHODS: This longitudinal analysis included 2491 medical visits from 809 white males enrolled between 1999 and 2013. The eGFR was calculated using the CKD-EPI and MDRD equations, and CKD cases were identified as those with an eGFR <60mL/min/1.73m(2). Gross beta activity measured by five monitors of the U.S. Environmental Protection Agency's RadNet monitoring network was utilized to represent PR. RESULTS: Ambient PR levels from 1 to 28days prior to clinical visit demonstrated robust negative associations with both forms of eGFR, but not with the increased odds of CKD. An interquartile range higher 28-day average ambient PR level was significantly associated with 0.83-mL/min/1.73m(2) lower eGFR estimated by the CKD-EPI equation (95% confidence interval: -1.46, -0.20
Keywords: Aged Glomerular Filtration Rate Humans Male *Radioactivity *Air pollution *ckd *Particle radioactivity *Renal function *eGFR